2008
DOI: 10.1097/jcp.0b013e31818d21cf
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Masked, Placebo-Controlled Study of Fluoxetine for Hypochondriasis

Abstract: This study assessed the efficacy, durability, and tolerability of fluoxetine for hypochondriasis, a disorder for which controlled pharmacological trials are scarce. Fifty-seven patients with hypochondriasis were enrolled: 12 discontinued during the placebo run-in, and 45 were randomized to either fluoxetine or placebo for 12 weeks (acute treatment). Responder status was defined as a Clinical Global Impression rating for hypochondriasis of much or very much improved. Secondary outcome measures included severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…Furthermore, duration, comorbidity and benzodiazepine use did not predict the course of hypochondriacal symptoms during the follow-up period. The results with regard to the efficacy of CBT or a pharmacological treatment with an SSRI are in concordance with the results of the recent placebo-controlled study of Fallon et al (2008) who concluded that fluoxetine is a moderately effective treatment for hypochondriasis with durable efficacy over a follow-up period of 6 months.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, duration, comorbidity and benzodiazepine use did not predict the course of hypochondriacal symptoms during the follow-up period. The results with regard to the efficacy of CBT or a pharmacological treatment with an SSRI are in concordance with the results of the recent placebo-controlled study of Fallon et al (2008) who concluded that fluoxetine is a moderately effective treatment for hypochondriasis with durable efficacy over a follow-up period of 6 months.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, paroxetine appeared to be as effective as CBT (Greeven et al, 2007). Recently, Fallon et al (2008) published a double-masked placebo-controlled study of fluoxetine for hypochondriasis. After a follow-up period of 6 months the improvement of patients taking fluoxetine was maintained and the percentages of responders in the fluoxetine and the placebo group still differed significantly from each other in the advantage of the fluoxetine group.…”
Section: Introductionmentioning
confidence: 98%
“…The condition is characterised by excessive concern over health, constant fear of undiagnosed disease that physicians may have missed, and the characteristic behaviours of repeated checking and need for medical reassurance. Pharmacological treatment is not normally acceptable to patients, as those with marked health anxiety are typically very sensitive to adverse effects of medication: but fluoxetine showed some benefit over placebo, though this was not pronounced and occurred late in treatment (8-12 weeks [I (PCT)] (Fallon et al, 2008). Psychological treatments have been found beneficial [I (M)] ( Thomson and Page, 2007), and include behavioural stress management (Clark et al, 1998) ([II]), cognitive behaviour therapy, in both face-to-face and internet format (Hedman et al, 2011b;Seivewright et al, 2008;Sørensen et al, 2011) (Tyrer et al, 2014).…”
Section: Marked Health Anxiety ('Illness Anxiety Disorder')mentioning
confidence: 99%
“…This follow-up study included all 58 patients from either of 2 SSRI treatment studies: 14 from an open-label study of fluvoxamine 5 and 45 from a double-masked, placebo-controlled trial of fluoxetine, 6 with one patient participating in both. These treatment studies recruited individuals through media advertisements and primary care clinic screenings.…”
Section: Participantsmentioning
confidence: 99%
“…Further details are available in previous publications. 5,6 Measures at Baseline and at Follow-Up At baseline, all participants were assessed with the Structured Clinical Interviews for DSM-III-R (later DSM-IV; SCID I and SCID II) for the diagnosis of Axis I and II disorders. Other assessments included the Whiteley Index for hypochondriasis severity, 9 the Beck Depression Inventory, 10 the Hamilton Anxiety Scale, 11 the Medical Outcomes Study 36-item Short-Form Health Survey for functional status, 12 and the Brief Physical and Sexual Abuse Questionnaire for history of traumatic events before age 16.…”
Section: Participantsmentioning
confidence: 99%